A case of tadalafil-induced fixed drug eruption - Bostan, Ecem; Gökalp, Fulya (Acta Medica, 2025)
Fixed drug eruption is a variant of adverse cutaneous drug eruptions which is characterized by the formation of dusky patches and plaques involving the skin and mucosa, following the ingestion of certain drugs such as non-steroidal anti-inflammatory drugs, metronidazole and cotrimoxazole. Herein, we would like to report an unusual case of tadalafil-induced fixed drug eruption.